2000
DOI: 10.1901/jaba.2000.33-373
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Parental Nonadherence in Clinical Behavior Analysis: Effective Treatment Is Not Enough

Abstract: Applied behavior analysts have developed many effective interventions for common childhood problems and have repeatedly demonstrated that childhood behavior responds to properly managed contingencies. The success of these interventions is dependent upon their basic effectiveness, as demonstrated in the literature, their precise delivery by the clinician to the parent, and adherence to or consistent implementation of the intervention. Unfortunately, arranging the consistent implementation of effective parenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
131
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(132 citation statements)
references
References 83 publications
1
131
0
Order By: Relevance
“…Behavior-analytic interventions must be implemented consistently and correctly to be highly effective (e.g., Allen and Warzak 2000;St. Peter Pipkin et al 2010;Vollmer et al 2008).…”
mentioning
confidence: 99%
“…Behavior-analytic interventions must be implemented consistently and correctly to be highly effective (e.g., Allen and Warzak 2000;St. Peter Pipkin et al 2010;Vollmer et al 2008).…”
mentioning
confidence: 99%
“…This is especially important with complex or difficult-to-implement procedures. Allen and Warzak (2000) suggest further in their work on parental adherence to treatment plans that the best outcome for consumers may be obtained with procedures that result in good outcomes and that are most likely to be adopted by persons providing care to the consumer; in some cases, such procedures may be more desirable than those that result in the best outcomes in the laboratory. The current study examined one component of one of a teaching procedure that previously had been shown to be effective and found the gradual fading of physical prompts to be an unnecessary component of MTLD.…”
Section: Discussion and Guidelines For Practitionersmentioning
confidence: 99%
“…The effectiveness of an intervention is limited by the factors related to its implementation; these include both precise and consistent implementation over time (Detrich 1999). Even when a teaching strategy is shown to be effective under ideal conditions, its success ultimately will depend on whether they are effective when implemented by the instructors and parents who use them (Allen and Warzak 2000;Axelrod 1991Axelrod , 1992. Allen and Warzak emphasize the importance of designing and promoting interventions that are as simple as possible, as treatment complexity has been suggested as interfering with treatment integrity and, presumably, learning.…”
mentioning
confidence: 99%
“…However, these challenges are not unique to an ASD diagnosis and are likely similar to the challenges faced by other multiplex families who have multiple children who engage in problem behavior and are seeking behavioral interventions (e.g., parents of children diagnosed with an intellectual disability or other developmental disorder). For example, many of the behavioral treatments that have been shown to effectively reduce problem behaviors (e.g., aggression, self-injury, destructive behavior) can also be quite laborious (Allen & Warzak, 2000). Such treatments can be highly effective (Campbell, 2003;Didden, Duker, & Korzilius, 1997;Heyvaert, Saenen, Campbell, Maes, & Onghena, 2014), but often include elements such as extinction (Iwata, Pace, Cowdery, & Miltenberger, 1994b), dense schedules of reinforcement (Hagopian, Boelter, & Jamolowicz, 2011), and close supervision.…”
mentioning
confidence: 99%
“…In addition, treatments may need to be implemented with the high integrity or very dense schedules of reinforcement when first introduced (St. Peter Pipkin, Vollmer, & Sloman, 2010), which may be challenging. Even under more straightforward circumstances in which parents only have one child who engages in problem behavior, caregivers sometimes struggle to implement such effortful treatments with good fidelity (Allen & Warzak, 2000). The additional stressors and need to divide their attention across siblings mean that multiplex families requiring treatment may be even more likely to find such effortful treatments to be unfeasible.…”
mentioning
confidence: 99%